"It's a delicate dance": understanding CSR relationships from the nonprofit perspective. Issue 2 (7th June 2019) - Harrison, Virginia
Abstract : Purpose: The purpose of this paper is to examine corporate social responsibility (CSR) partnerships from the often-overlooked perspective of nonprofit beneficiaries, situated in the rapidly evolving higher education funding environment. Design/methodology/approach: In-depth interviews with corporate relations officers from public research universities across the USA were conducted. Qualitative coding procedures from Lindlof and Taylor (2019) were employed to analyze transcript data. Findings: Three main factors have contributed to a rapidly evolving climate for corporate partnerships: CSR partnerships help universities build their reputations rather than endowments; feature new preferences in communication-based stewardship practices; and raise questions about university autonomy and authority. Research limitations/implications: New interpretations of interdependent relationships and stewardship may be needed to explain new corporate funding models, while threats to nonprofit organizational authority and autonomy may be growing. Practical implications: Nonprofit practitioners may better understand how to position their organizations as more attractive to corporations while learning how to advocate for mutual benefits. They may also benefit from a new understanding of corporate stewardship. Originality/value: While previous research has documented detrimental effects to nonprofits in CSR partnerships, higher education fundraisers in this study detail their struggles with new models of measuring success, new expectations for stewarding corporate partners and perceived threats to autonomy. Their voices add to a fuller understanding of rapidly evolving relationship management practices in higher education.